Evaluating the prescribing and management practices of clozapine at a public sector psychiatric hospital - Mukoko, Vimbisai Millicent (Rhodes University, Faculty of Pharmacy, Pharmacy)
Approximately one percent (1%) of the South African population suffers from schizophrenia. Clozapine has proven to be more effective than conventional antipsychotics in the treatment of schizophrenia, particularly in alleviating positive symptoms. Clozapine is primarily indicated for treatment-resistant schizophrenia due to its severe adverse effect profile. The prescribing guidelines recommend a trial of at least two different antipsychotic drugs before the initiation of clozapine. At least one should be a non-clozapine second generation antipsychotic. Compared to other atypical antipsychotics, clozapine poses the greatest risk of causing a haematological event, such as neutropenia and agranulocytosis. Agranulocytosis (estimated prevalence of 1.3%) is a life-threatening adverse effect. Common adverse effects include weight gain and metabolic syndrome, hypersalivation and constipation. These can also predispose the patient to co-morbid diseases which further complicate their current diagnosis. Haematological and metabolic monitoring is paramount throughout the duration of clozapine therapy. International (NICE guidelines, Clozapine REMS, and Maudsley prescribing guidelines) and national (South African STGs, SASOP treatment guidelines and the SAMF) guidelines recommend these monitoring patterns to assist with the prevention and management of the adverse effects of clozapine.
Keywords: Clozapine; Schizophrenia -- Chemotherapy; Schizophrenia -- South Africa -- Treatment